The Effect of Lower-Body Strength Training Using Ankle Weights on the Straight-Kick Ability of Athletes from the IKSPI Kera Sakti Timika - Wahyuni, Baiq Sri; Sutirta, Habibi; Letisia, Maria (Yayasan Insan Mulia Bima, 2026)
In general, Pencak Silat techniques include punches, kicks, grabs, throws, takedowns, locks, blocks, backhand strikes, scratches, thrusts, strikes, slashes, and jabs. (Gunawan. A, 2007). A physical component that plays a significant role in every sport, including Pencak Silat, is lower-body explosive power. Ankle weight training is an exercise designed to enhance the strength and performance of the lower-body muscles, performed by applying weight to the lower legs (Girsang & Hasibuan, 2012). The research was conducted at the IKSPI Kera Sakti Pencak Silat Academy in Timika, Papua. This was a pre-experimental study. The design was a one-group pretest-posttest design. The results of this study indicate that there is a significant effect of lower-body power training using the ankle-weight method on the straight-kick ability of athletes from the IKSPI Kera Sakti Timika, as evidenced by a pretest average score of 10.13, which increased in the posttest, with the average score for straight-kick ability reaching 15.20. The t-test results also show that the calculated t-value of 8.264 > the critical t-value of 1.7613 (df 14), with a significance level of p = 0.000 < 0.05. Based on the research results, it is concluded that “There is a significant effect of lower-body muscle power training using the Ankle Weight Method on straight-kick ability among athletes at the IKSPI Kera Sakti Timika.